2022
DOI: 10.1002/macp.202100410
|View full text |Cite
|
Sign up to set email alerts
|

Functional Applications of Polymer Electrolytes in High‐Energy‐Density Lithium Batteries

Abstract: Polymer electrolytes have attracted great interest in advanced lithium batteries. Recently, it has been found that there are many functional applications of polymer electrolytes in lithium batteries, which are very important for the development of high-energy-density lithium batteries. In this review, the functional applications of polymer electrolytes are reviewed in terms of protecting lithium metal anode, coating for high-voltage cathodes, and improving the safety of batteries. Finally, the remaining challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…On the contrary, as schematized in Figure b, LSKL–chitosan and LS–chitosan GPEs show a semi-ductile behavior characterized by E values ranging from 55 ± 4 to 940 ± 63 MPa and ε b values of 14.1 ± 0.2 to 43.9 ± 21.1% (Figure c,d). For the sake of comparison, the most widely exploited GPE, the polyethylene oxide/LiTFSI blend, displays a Young’s modulus of ∼100 MPa . Independently of the composition, we found that glutaraldehyde cross-linking increases stiffness and lowers ductility due to the formation of extended imine linkages in the electrolyte.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…On the contrary, as schematized in Figure b, LSKL–chitosan and LS–chitosan GPEs show a semi-ductile behavior characterized by E values ranging from 55 ± 4 to 940 ± 63 MPa and ε b values of 14.1 ± 0.2 to 43.9 ± 21.1% (Figure c,d). For the sake of comparison, the most widely exploited GPE, the polyethylene oxide/LiTFSI blend, displays a Young’s modulus of ∼100 MPa . Independently of the composition, we found that glutaraldehyde cross-linking increases stiffness and lowers ductility due to the formation of extended imine linkages in the electrolyte.…”
Section: Resultsmentioning
confidence: 79%
“…For the sake of comparison, the most widely exploited GPE, the polyethylene oxide/LiTFSI blend, displays a Young's modulus of ∼100 MPa. 15 Independently of the composition, we found that glutaraldehyde cross-linking increases stiffness and lowers ductility due to the formation of extended imine linkages in the electrolyte. An increased fraction of lignin lowers both E and ε b values as reported for chitosan-lignin films, 49,50 while the micellar LSKL dispersion results in stiffer but more brittle GPEs in comparison with LS−chitosan GEPs.…”
Section: ■ Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Energy density and safety performance have become two bottle-neck issues for the state-of-the-art lithium-ion battery technology along with its explosive applications in energy storage grids and electric vehicles. The replacement of graphite anode with lithium metal creates a huge space to lift the energy density because of the superior theoretical capacity of lithium (3860 mA h g –1 ) compared to graphite (370 mA h g –1 ). , However, there are four safety problems in the lithium metal anode, including dendrite growth, migratory intermediate species, unstable SEI layer, and infinite volume change . Among them, the formation of lithium dendrite is considered to be the main reason for the failure of the lithium metal anode, which causes short circuit .…”
Section: Introductionmentioning
confidence: 99%